The mediating effect of self-efficacy on social support and cancer screening behavior among Chinese women: a cross-sectional study - Hanqing Tu; Linping Zhang; Mengjiao Xu; Ziyan Zhao; Jing Han; Liang Yan (BMC, 2024)
Abstract Background Breast and cervical cancer are the most common cancers in women, and are associated with high morbidity and mortality rates. Cancer screening can facilitate early diagnosis, reduce mortality, and ease the burden of cancer. Social support and self-efficacy are strongly associated with cancer screening behavior. The present study aimed to explore the mediating effect of self-efficacy on social support and cancer screening behavior. Methods In this cross-sectional survey study conducted from June to October 2023, 312 women aged 35-65 years were recruited from the East Coast area of China. A general information questionnaire, cancer screening behavior questionnaire, social support scale and self-efficacy scale were used to collect data. Descriptive statistics were used to analyze the general characteristics of participants; one-way analysis of variance was used to test for differences in the measured variables; and Pearson's correlation analyses were used to describe the relationship among social support, self-efficacy, and cancer screening behavior. A mediation model was constructed and analyzed using the PROCESS macro for SPSS. Results The mean (standard deviation) screening behavior score for breast cancer and cervical cancer was 3.98 (2.79), representing an intermediate level. Self-efficacy was closely related to social support and cancer screening behavior. Social support showed a significant positive correlation with self-efficacy (r = 0.37, p < 0.01) and cancer screening behavior (r = 0.18, p < 0.01). Self-efficacy was also significantly positively correlated with cancer screening behavior (r = 0.19, p < 0.05). Self-efficacy showed a full mediating effect between social support and cancer screening behavior, with an explanatory power of 32%. Conclusions The findings emphasize the need to increase women's level of social support and self-efficacy, which in turn can increase women's participation in breast and cervical cancer screening.